Chondrosarcoma of Dorsal Spine: A Case Study - Alam, Md. Shafiul; Alam, AKM Jakirul; Hasan, Md. Rejaul; Farzana, Tayseer (Journal of Science Foundation, 2016)
Chondrosarcoma is a type of tumor originated from cartilage and bone. About 30% of skeletal system cancers are chondrosarcomas and less than 10% of all chondrosarcomas occur in the spine. It is resistant to chemotherapy and radiotherapy. Total resection ensures early recovery and prevents recurrence. This author presents a case of chondrosarcoma of spine diagnosed by MRI and histopathology. Journal of Science Foundation, January 2016;14(1):30-33